Faith in film: religious themes in contemporary cinema - Deacy, Christopher (Routledge, Taylor & Francis Group, 2016)
Christianity and film in conversation -- The heart of the matter : escapism vs. religion -- Theological currents in contemporary cinema : seven case studies -- Movie gods and goddesses : the role of the celebrity -- The 'passion' of the audience -- New ways forward